Genetic screening of TGFBI in Iranian patients with TGFBI-associated corneal dystrophies and a meta-analysis of global variation frequencies. (4th July 2022) - Jozaei, Roxanne; Javadi, Mohammad-Ali; Safari, Iman; Moghaddasi, Afrooz; Feizi, Sepehr; Kanavi, Mozhgan Rezaei; Najafi, Sajad; Safdari, Bahareh; Salahshourifar, Iman; Elahi, Elahe; Suri, Fatemeh
ABSTRACT: Purpose: Transforming growth factor beta-induced ( TGFBI )-associated corneal dystrophies (CDs) are a clinically heterogeneous group of CDs caused by mutations in the TGFBI gene. Nucleotide sequences encoding two arginine residues at positions 124 and 555 in TGFBI protein are mutation hotspots. We screened regions of TGFBI that include the hotspots in a cohort of Iranian patients with TGFBI -associated CDs. We also performed a meta-analysis for frequencies of all reported TGFBI mutations. Methods: Twenty-four TGFBI -associated CD-diagnosed patients were recruited. Exons 4 and 12 of TGFBI were amplified by the polymerase chain reaction and sequenced by Sanger protocol. A meta-analysis on reported TGFBI sequence data was done by reviewing all published relevant articles available in NCBI. Results: Twenty-two out of 24 patients had mutations in exons 4 or 12 of TGFBI . The most frequent mutations were p.Arg124Cys, p.Arg124His, and p.Arg555Trp; each of these was found in six families. Three other missense mutations including p.Arg555Gln, p.Ile522Asn, and p.Ala546Thr were also identified. The data suggested a fairly tight genotype/phenotype correlation for the most common CDs. Literature review evidenced that the reported mutations affected less than 30% of the amino acids of the TGFBI protein and that p.Arg124His, p.Arg124Cys, p.Arg555Trp, p.Arg124Leu, p.Arg555Gln, and p.His626Arg were the most frequent mutations. Conclusion: TGFBI mutation profile of Iranian patients is very similar to that of the rest of the world. The meta-analysis confirmed the worldwide prevalence of p.Arg124 and p.Arg555, showed that p.His626Arg is also relatively frequent, and evidenced the value of screening exons 4 and 12 of TGFBI .